Electrical behavior of exploding copper wire in ambient air - Barbaglia, Mario Oscar (2018)
This work experimentally investigates the electrical behavior of an exploding wire when the initial energy of the system varies from 28 to 709 J. This experiment uses 50-um-diameter, 33-mm-long copper wires. The wire is surrounded by air at normal atmospheric pressure and temperature. The experiment monitored the current derivative, voltage between wire ends, total visible radiation emitted, and the shadow image of the wire to study how the electrical parameters vary as a function of initial energy. The results indicate a change in the initial discharge mechanism.